(1 − 2u_2)-Constacylic Codes over F_p + uF_p + u^2F_p (European Journal of Pure and Applied Mathematics, 2016)
Let F_p be a finite field, where p is an odd prime, and let u be an indeterminate. This article studies (1 − 2u^2)-constacyclic codes over the ring F_p + uF_p + u^2F_p, where u^3 = u. We describe generator polynomials of this kind of codes and investigate the structural properties of these codes by a decomposition theorem.